The Effect of Return on Asset and Current Ratio on Stock Returns - Utami, Tri; Hendaryan, Dudi (Almana : Jurnal Manajemen dan Bisnis, 2024)
Increasing Stock Return on the company is something that investors expect because when the company has a high Stock Return value, investor welfare will increase. This study aims to analyze and test how much influence Return On Assets (ROA) and Current Ratio (CR) have on Stock Returns. This Study uses secondary data presented on the IDX. The population in this study was 41 tourism companies. The sample used was a purposive sampling method obtained from 15 tourism companies. The analysis method used is panel data regression analysis, classical assumption test, and hypothesis testing using the t-test and f-test. In analyzing the data, this study uses the Econometric Views (Eviews) version 12 program tool. The results showed that Return On Assets (ROA) partially had no effect on Stock Returns. While the Current Ratio (CR) partially affects Stock Returns. Simultaneously Return on Assets (ROA) and Current Ratio (CR) have a significant effect on Stock Returns. This is influenced by other variables that are not included in this study.